Prospective Teachers' Beliefs About Human Intelligence in a Turkish Sample - KAYA, FATİH; Kaya, M. Talha; Kaya, Sümeyye (Sage Publications Inc., 2023)
Research consistently reports a moderate to a strong relationship between intelligence and academic performance. For about a century, the concept of intelligence has often been used in the definition of giftedness and the identification of gifted students along with other data sources, although some experts are against it. An understanding of prospective teachers' beliefs about intelligence is important to unearth how they perceive intelligence and giftedness. We replicated Warne and Burton's (2020) study with 157 prospective Turkish teachers. They were selected using an online convenience sampling method from various departments of a faculty of education. Of the participants, 72.6% were female and 27.4% were male. We adapted Warne and Burton's (2020) survey, translating it to Turkish and administered it online to understand the prospective teachers' beliefs about intelligence as well as to examine if these beliefs differ across cultures. We found that the prospective teachers' understanding was mostly in line with the original study as well as the mainstream views of intelligence. We also found similar results to the original study, regarding the components of intelligence. Like the original study, the Turkish sample showed an understanding of the relationship between education and intelligence; however, the items about biological and genetic influences on intelligence, the plausible causes of group differences, the life outcomes of intelligence, and a cross-cultural comparison of intelligence had a low response uniformity in both studies. Similar findings across samples may be attributed to common, popular views as well as similar textbooks or other resources used in both cultures. The samples (e.g., educational level and age) may be partially responsible for the differences in the findings across both cultures.
Keywords: Intelligence; Gifted; Survey; Replication Research; Cultural Context